Unique branching pattern of aortic arch in a patient with aortopulmonary window - Bhat, Venkatraman (BJR Case Rep, 2016)
Aortic arch (AA) anomalies are usually associated with congenital heart disease. Variations such as aberrant subclavian artery have significance if shunt surgery is planned. Other variations may be clinically insignificant or present with respiratory or oesophageal symptoms. Demonstration and understanding of arch anomalies are crucial for managing as well as improving our understanding of their embryological basis. This presentation illustrates an unusual branching pattern of AA in a patient with an aortopulmonary window in which five arteries independently arose from the AA. CT imaging appearance of the anomaly is illustrated. A brief description of the embryological basis and significance of the anomaly is presented.